Competency, task and learning-based teaching. The case of legal translation Portuguese-Spanish - Galán Mañas, Anabel (Íkala, Revista de Lenguaje y Cultura, 2007)
This paper presents some of the aspects that should be taken into account in the design of a proposal for teaching translation: the necessary competences, the pedagogical conception, the learning context, the learning objectives and contents, the teaching progression, the didactical units and the different types of assessment. Although these guidelines may be helpful in designing any translation course, we are focusing on legal translation from Portuguese into Spanish. The legal systems involved are those from Spain, Portugal and Brazil. Received: 31-03-07 / Accepted: 30-07-07 How to reference this article: Galán Mañas, A. (2007). La enseñanza por competencias, por tareas y por objetivos de aprendizaje: el caso de la traducción jurídica portugués-español. Íkala. 12(1), pp. 27 – 57.